2016
DOI: 10.1089/cap.2015.0072
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Temper and Irritability: The Relationship to Tantrums in a Community and Clinical Sample

Abstract: Background: This study explores the relationship of irritability to tantrums and loss of temper in a community and clinical sample. Methods: The community sample, recruited via commercial mailing lists, consisted of 462 6-year-olds whose parents completed the Child Behavior Checklist (CBCL), and Preschool Age Psychiatric Assessment (PAPA). Tantrums were assessed in the oppositional defiant disorder (ODD) section of the PAPA. Irritability was assessed in the depression section to identify persistently irritable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 41 publications
4
28
0
1
Order By: Relevance
“…This was also consistent with the duration and frequency rates of outbursts displayed by TD children (Österman & Björkqvist, 2010). It is, however, dissimilar to rates of outburst in clinical populations, where outburst rates are much higher in boys than girls (Carlson et al, 2016;Potegal et al, 2009). Examining the differences in symptoms across genetic subtypes is important for elucidating causal mechanisms.…”
Section: Are Pws Outbursts Influenced By Age Gender or Genetic Subtype?supporting
confidence: 70%
“…This was also consistent with the duration and frequency rates of outbursts displayed by TD children (Österman & Björkqvist, 2010). It is, however, dissimilar to rates of outburst in clinical populations, where outburst rates are much higher in boys than girls (Carlson et al, 2016;Potegal et al, 2009). Examining the differences in symptoms across genetic subtypes is important for elucidating causal mechanisms.…”
Section: Are Pws Outbursts Influenced By Age Gender or Genetic Subtype?supporting
confidence: 70%
“…Epidemiological data suggest that the 3‐month prevalence of DMDD ranges from 0.12% to 9%, depending upon the age range studied and whether a symptom‐based proxy of DMDD or diagnostic criteria are used (Althoff et al., ; Copeland et al., ; Dougherty et al., ; Mayes, Waxmonsky, Calhoun, & Bixler, ). In clinical samples, the prevalence is higher, ranging from 26% to 30% (Axelson et al., ; Gabrielle A Carlson, Danzig, Dougherty, Bufferd, & Klein, ; Margulies, Weintraub, Basile, Grover, & Carlson, ). The most recent prevalence estimates of DMDD were derived from extant items collected as part of the National Comorbidity Survey – Adolescent Supplement (NCS‐A) where a total of 310 of 6,483 adolescents (5.26%) met DMDD criteria when exclusionary criteria were not considered and frequency of outbursts was lower than required by the DSM (Althoff et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…What behaviors characterize severe outbursts in children under age 13? Using an Irritability Rating Scale that has been part of our standardized outpatient assessment for the past decade, 9 I found that parents of 303 children being evaluated for rages reported that 87% of children wrecked property, 77% threw things, 63% hit/kicked and/or spit during their outbursts, 64% threatened others, 39% hurt themselves, and 34% of parents said that they have had to physically restrain their child. Almost three-fourths (72%) said that these outbursts occurred daily to weekly!…”
mentioning
confidence: 99%